The Role of Customer Satisfaction in Improving Pharmacy Performance" - Johnson; Laksmidewi, Dwinita (Jurnal Manajemen, 2024)
This study aims to analyze the influence of pharmacist attitude, medication supply, pharmacy location, and price fairness on customer satisfaction and its impact on pharmacy performance in independent pharmacies. In conducting testing of these variables, the researcher distributed questionnaires to 345 respondents who had visited, consulted with pharmacists or pharmacy staff, and purchased medication at the pharmacy, using a Modified Likert scale. The sample was collected using a purposive sampling method. Data analysis was conducted using the Structural Equation Model (SEM) Smart PLS. The results of the study indicate that pharmacist attitude, medication supply, pharmacy location, and price fairness have a significant direct impact on pharmacy performance. Furthermore, pharmacist attitude, medication supply, pharmacy location, and price fairness have a significant direct impact on customer satisfaction. Customer satisfaction has a significant direct impact on pharmacy performance. Customer satisfaction also mediates the effect of pharmacist attitude, medication supply, pharmacy location, and price fairness on pharmacy performance.